(untitled) (Journal of Engineering, 2012)
The paper presents an investigation to the flutter speed of composite wing for different ply orientation. Structurally the composite wing was idealized as a composite beam load carrying structure. Theodorsen’s expression was used to get the 2- dimension unsteady lifting force and pitching moment in the limit of incompressible flow and subsonic speed which were integrated over the wing span. A free vibration analysis was first carried out to get the natural frequencies and mode shapes .The velocity-damping (V-g) method was used to calculate the flutter speed and the flutter frequency. A wing of unmanned aerial vehicle was manufactured from woven glass and polyester resin where the flutter speed was calculated experimentally by the wind tunnel test .The flutter speed was calculated analytically for different ply orientation, it is found that the increasing in torsion rigidity leads to increase in the flutter speed, the fiber combination with high torsion rigidity and relatively low coupling rigidity give higher flutter speed.